MORPHOMETRIC STUDY OF SWANGGI FISH (Priacanthus tayenus ,Richardson, 1846) IN CITUIS WATERS, BANTEN - Ruzanna, Arina; Syahrial, Syahrial; Khalil, Munawar; Ayuzar, Eva; A’kla, Cut Meurah Nurul; Agustini, Nella Tri; Ikhsan, Nur (Politeknik Kelautan dan Perikanan Dumai, 2025)
Priacanthus tayenus fish, often referred to as Swanggi, were found during fishing activities in the Cituis area, Banten. This indicates that the potential population of this fish remains substantial and has high economic value. A total of 30 fish were obtained, consisting of 11 female fish and 19 male fish. This study used the purposive sampling method. Analysis of the relationship between the length and weight of Swanggi fish from the waters of Cituis showed a correlation coefficient (r) of 0.9305. This figure indicates that the growth of the Swanggi fish is isometric. The length of the Swanggi fish (PB) increases with increasing morphological size. Food availability is thought to influence these correlation results. The availability of food plays a crucial role in the growth process. These correlation results indicate that food availability in the waters is still sufficient to support the life of the Swanggi fish.